Buckling of conductive layer within shape memory matrix - Tan, Zhong Jie (2017)
This report explores one of the most important type of polymers widely used in the industry, shape memory polymers (SMPs). SMPs has an unique ability called the shape memory effect (SME) which allows them to recover their original shape under an external stimulus such as heat even though their temporary shape is distorted. In this report, only two different types of SMPs were studied intensively, silicone with melting glue and silicone with thermoplastic polyurethane (TPU).